Studies on sorption and regeneration of granulated cork for oil and grease removal - Pereira, J. (2014)
The aim of this work is to develop a method to recover sorbed oil and grease from granulated cork, in order to promote biomass regeneration. Experimental procedure involved biomass saturation with oil, followed by chemical regeneration. Oil removal by elution was tested using HNO3 and NaOH solutions, cationic and anionic surfactants and organic solvents, namely carbon tetrachloride and n-hexane. Chemical desorption efficiency using organic solvents achieved values of 90 ± 6 % and 72 ± 6 % for CCl4 and n-hexane, respectively. Although the use of organic solvents proved to be an efficient process, it involves high costs and a negative environmental impact. Physical regeneration could be an alternative to the use of solvents for oil removal from granulated cork.